Creativity, Inc. : overcoming the unseen forces that stand in the way of true inspiration - Catmull, Ed, ....-; Wallace, Amy, ....- (New York, NY : Random House, 2023)
The co-founder and longtime president of Pixar updates and expands his 2014 New York Times bestseller on creative leadership, reflecting on the management principles that built Pixar’s singularly successful culture, and on all he learned during the past nine years that allowed Pixar to retain its creative culture while continuing to evolve.
Keywords: Business management